Analysis on top-down and bottom-up mechanisms in visual search - Nithya Hariharan (Nanyang Technological University, 2025)
Humans engage in visual activity on a daily basis. Searching for a target in a cluttered space is a common human activity.Visual search, the act of locating a target within a cluttered environment, is a fundamental component of human visual behavior. There are different forms in which visual search takes place. Active research in this field have proposed using top-down and bottom-up approaches to replicate the model of visual search computationally. However, many current models treat these mechanisms in isolation or integrate them in a limited manner, resulting in behavior that diverges from human search patterns. This paper conducts a systematic analysis of prominent visual search models, with a primary focus on their strategies for integrating bottom-up and top-down processes.